SYSTEM OF PENSION PROVISION IN UKRAINE: STATE, PROBLEMS AND POSSIBLE WAYS OF SOLUTIONS (INNOVATIVE ECONOMY, 2026)
Fedoryshyna L.M., Pikhniak T.A. SYSTEM OF PENSION PROVISION IN UKRAINE: STATE, PROBLEMS AND POSSIBLE WAYS OF SOLUTIONSPurpose. The aim of the article is to study the current pension system in Ukraine and assess its state, as well as identification of the main problems and outline of possible ways to solve them.Methodology of research. A set of general scientific and special research methods was used to achieve the set goal. In particular, methods of analysis and synthesis, generalization, abstract and logical ‒ for studying the theoretical foundations of the functioning of the pension system and processing scientific publications and regulatory legal acts regulating pension relations in Ukraine; monographic ‒ for studying the scientific approaches of domestic and foreign researchers to the problems of development and reform of the pension system; statistical ‒ for assessing the current state of pension provision, studying the dynamics of the number of pensioners, the structure of pension payments, the average size of pensions, as well as for analysing regional and gender features of pension provision; comparative ‒ to compare indicators over time and across regions, as well as to assess differences between individual categories of pension recipients; systematization and generalization ‒ to identify the main problems of the functioning of the pension system of Ukraine and substantiate the directions of its further reform; tabular and graphical ‒ to visually present the results of the study, in particular the dynamics and structure of pension indicators.Findings. The current state of the pension system in Ukraine was analysed, in particular, the main principles of its functioning and the structure of the three-tier pension system were studied. It was established that in practice in Ukraine the solidarity level of the pension system mainly functions, while the accumulative level is at the stage of implementation. The dynamics of the number of pensioners in recent years was analysed, which showed a tendency to a gradual reduction in their number. The main indicators of pension provision were assessed, in particular the average size of pension payments, the structure of pensions by type and the level of differentiation of pension incomes.Significant differences in the size of pension payments between different categories of recipients, regions and by gender were identified. The main problems of the functioning of the pension system of Ukraine were identified based on the analysis, including: a significant financial burden on the solidarity level, the budget deficit of the Pension Fund, demographic challenges and insufficient development of funded and non-state pension provision. The directions for improving the pension system were substantiated.Originality. The study of structural and social problems of the pension system of Ukraine and the formulation of directions for their solution related to ensuring the financial stability of the system, the transition to a multi-component provision model, improving demographic and employment policies, increasing social justice and eliminating inequality, institutional and managerial modernization, and implementing educational and information policies have been further developed.Practical value. The research results can be used to improve the mechanisms for calculating pensions and managing financial resources of the Pension Fund of Ukraine, as well as to prepare for the implementation of a funded pension system, which will increase the efficiency of the system and reduce social inequality among pensioners.Key words: pension provision, pension system, pension, social injustice, inequality, pensioners, budget deficit, income differentiation, non-state pension provision.
Keywords: pension provision; pension system; pension; social injustice; inequality; pensioners; budget deficit; income differentiation; non-state pension provision